1989
DOI: 10.1111/j.1464-410x.1989.tb05160.x
|View full text |Cite
|
Sign up to set email alerts
|

Trial without Catheter following Acute Retention of Urine

Abstract: A total of 60 patients with acute urinary retention were studied to establish whether a trial without a catheter was justified and to identify subgroups of patients most likely to benefit from this practice. The patients were randomly allocated to 3 groups; the catheters were removed either immediately after the bladder was emptied, or 24 or 48 h later; 17 patients urinated satisfactorily after removal of the catheter. Re-establishment of micturition was not associated with the length of history or severity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
3
4

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(63 citation statements)
references
References 9 publications
1
55
3
4
Order By: Relevance
“…Over a decade later, in another retrospective study, Breum et al [4] reported an incidence of surgery of 84% at 5 years within their cohort of 70 patients. Prospective studies in this area are sparse and often provide a short follow-up of few patients [5]. Klarskov et al [6] reported the longest follow-up to date in a prospective study of 1 year with a surgical intervention rate of 85%; in that study of 228 men with AUR they reported that factors predictive of preserved voiding ability after a successful TWOC were a retained volume of < 500 mL, a maximum flow rate of > 5 mL/s, and the presence of an event thought to provoke AUR.…”
Section: Discussionmentioning
confidence: 99%
“…Over a decade later, in another retrospective study, Breum et al [4] reported an incidence of surgery of 84% at 5 years within their cohort of 70 patients. Prospective studies in this area are sparse and often provide a short follow-up of few patients [5]. Klarskov et al [6] reported the longest follow-up to date in a prospective study of 1 year with a surgical intervention rate of 85%; in that study of 228 men with AUR they reported that factors predictive of preserved voiding ability after a successful TWOC were a retained volume of < 500 mL, a maximum flow rate of > 5 mL/s, and the presence of an event thought to provoke AUR.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 60 patients with AUR in whom the catheter was removed no later than 48 h after catheterization, 17 patients (28%) voided successfully [56]. When these 17 patients were followed up for 6 months, six had required prostatectomy for severe LUTS while 11 had no or only minor symptoms.…”
Section: A Trial Without Cathetermentioning
confidence: 99%
“…While some have found no difference in success rates at 24 and 48 h, 32 others have suggested a benefit to waiting longer, particularly in men with large residual volumes 41 l. 33 It has recently been suggested that prostate size 427.5 g, residual volume 41 l and age 475 y may reduce the chance of successfully voiding after a TWOC. 34 It has also been suggested that the use of an alpha blocker may improve the success rate of a TWOC.…”
Section: Treatment Catheterisationmentioning
confidence: 99%